Primeiro registro de Rhinella pygmaea (Myers & Carvalho, 1952) para o município do Rio de Janeiro, RJ, e ameaças à sua conservação - Antônio Lourenço Pontes, Jorge; Mendonça Regio, Luiz Eduardo (Herpetologia Brasileira, 2026)
Rhinella pygmaea is an endemic anuran of the Atlantic Forest in the states of Rio de Janeiro and Espírito Santo, which spends most of its life buried in sandy soils. Little is known about its natural history or the occurrence of populations within its distribution range, especially in areas subject to intense anthropogenic pressure due to human occupation. Here, we report the first record of a population in the municipality of Rio de Janeiro, at a locality that was theoretically protected within the Environmental Protection Area of the Serras de Inhoaíba, Cantagalo, and Santa Eugênia. After this record, part of the habitat occupied by this population was removed from the conservation unit by the Rio de Janeiro City Hall. The area was subsequently designated for the establishment of an urban park and other land uses, rendering the future of the species in the municipality uncertain.